UMP and NUS – a gateway program - Fatmawati, Adam (Pejabat Naib Canselor, 2016)
A total of 24 students and two lecturers from Faculty of Chemical & Natural Resources Engineering (FKKSA) Universiti Malaysia Pahang (UMP) participated in an academic mobility program to the Department of Chemical and Biomolecular Engineering (ChBE), National University of Singapore (NUS) on April 17, 2016.